THE ROLE OF SOCIAL MEDIA AS A BUSINESS MARKETING EFFORTS ONLINE IN ONLINE SHOP NITHALIAN COLLECTION - Puji Muniarty; Nur Fetiningsih Syaframis; Novitasari Devi; Khaerunnisa; Azizah Sarifatul Nuraini; Ahmad Maulana (Program Studi Akuntansi, 2021)
This research method uses a qualitative descriptive method which aims to determine the Role of Social Media as an Online Shop Business Marketing Effort. This research uses a descriptive research approach using a qualitative approach. The research subject is the Nithalian Collection Online Shop Seller who is asked to provide information about a fact or opinion. The results in this study are in accordance with the research that the researchers conducted by following the nithaliancollection on Facebook. Nitalian Collection itself sells products ranging from make-up to robe under its own brand and other brands. What attracts the attention of this research is that social media from Nithaliancollektion is very thematic and neat, this is one of the factors that will influence enthusiasts of online shop to shop through social media. What's more interesting is that Nithaliancollection always reviews its merchandise in detail in the form of videos and photos on the Facebook-story, a good form of marketing effort made by Nitalian Collection is to write clearly in the bio description. Judging from social media nithaliancollektiondi, it is proven that social media is now very influential in making online shops. However, the online shop's social media must also be very well organized, have an attractive theme, and be consistent in order to attract customers to buy goods at the online shop. Online business is indeed much easier and cheaper than opening a regular store, in terms of business capital, it can save some funds.